Planowanie przez rodziców przyszłości ich dzieci z głęboką niepełnosprawnością intelektualną a wsparcie społeczne - Gałuszka, Izabella (Kultura-Społeczeństwo-Edukacja, 2025)
The arrival of a child with a disability into the world is a challenging experience for their parents. Addition-ally, the information about a diagnosis of profound intellectual disability intensifies this experience. This situ-ation significantly affects the family’s functioning. From the very beginning, both parents and siblings have many questions regarding the child’s present and future (Tylewska-Nowak, 2010). The Polish education system provides for the implementation of early developmental support for children and rehabilitative-edu-cational activities for participants with profound intellectual disabilities. These activities can be conducted at the place of residence or in a specialized facility. Support from the state and specialists becomes essential for the family. Families raising children with disabilities can access various forms of support that increasingly meet their needs year by year. Informational, institutional, or financial assistance positively influences the functioning of the family. Undoubtedly, contemplating what will happen after the “education” of a child with profound intellectual disabilities concludes accompanies the life experiences of their parents.The aim of the article is to present the results of research regarding the future of children with pro-found intellectual disabilities as expressed by their parents. The research inquiries presented indicators concerning the percentage of parents planning their future and their child’s future, as well as the similari-ties and differences related to these plans, taking into account the child’s age, the parent’s age, and the form of “education” being undertaken. The study also sought a connection between future planning and the subjective assessment of the social support received. The research was conducted using a mixed-methods strategy. The study group consisted of 60 families raising children with profound intellectual disabilities aged up to 25 years, residing in the Małopolskie Voivodeship.